PHYSICAL DEVELOPMENT OF PREPARATORY GROUPS CHILDREN AT PRESCHOOL EDUCATIONAL INSTITUTIONS IN KEMEROVO - Нина Константиновна Перевощикова; Илья Александрович Селиверстов; Светлана Альбертовна Дракина; Наталья Степановна Черных (The Publishing House Medicine and Enlightenment, 2020)
The purpose of the research is to study the social status and physical development level of children attending preparatory groups at preschool educational institutions. Materials and methods. We have observed 603 children attending preparatory groups of preschool educational institutions in Kemerovo, including: 6-year-old boys (n = 181, average age 6 years and 6 months ± 3.33 months), 7-year-old boys (n = 132, 7 years and 2 months ± 1.74 months), 6-year-old girls (n = 174, 6 years and 6 months ± 3.13 months), 7-year-old girls (n = 116, 7 years and 2 months ± 1.85 months). The examination was carried out on the basis of the Health Center of the Kemerovo City Children's Clinical Hospital N 1. The social status of families has been studied. Anthropometric parameters of all children have been studied to assess their physical development. The anthropometry outcome logging and analysis have been carried out with a special module (for children) of computer programs «Antropo 2009 1.3.0.5». Results. In the research of the physical development of preparatory groups children at preschool educational institutions in Kemerovo, statistical differences have been revealed between the age groups of 6 and 7-year-old boys and girls. There are no sex differences. Physical development at age period of 6-7 years has been defined as heterogeneous, which has required a differentiated approach to its assessment. Height parameters in children from the social group of single-parent families were statistically significantly lower in comparison with children from complete families. Conclusion. The age of 6 years old children is defined as «critical» in relation to the anthropometric parameter «height». The age of 7 was characterized by the prepubescent growth spurt phenomenon. Physical development assessment of preparatory groups children at preschool educational institutions requires a differentiated approach: to assess the physical development of 6-year-old children the method of centile tables (non-parametric) is recommended to use; to obtain the most accurate results for 7-year-old children the method of standard deviation (SD) (parametric) is recommended.